Struggle For Life Of Kate In Nick Cassavete's My Sister's Keeper Movie (2009) : A Humanistic Approach - NURVITA., AJENG RIZA (2012)
This study concerns with the movie entitled My Sister's Keeper which is directed by Nick Cassavetes. The Analysis of this research paper is focused on the major character, Kate Fitzgerald, based on structural elements and humanistic perspective. This research is conducted by using qualitative method. The object of this study is My Sister's Keeper movie by Nick Cassavetes. In this method, the writer uses two data sources, namely primary and secondary data source. The primary data is the movie itsefl and the secondary data are the other data which have relationship with the study, such as the articles from internet, the books and other relevant information. The outcome of the study shows the following conclusions. Firstly, based on the structural analysis, it is indicated that each of narrative and technical element present a unity. Secondly, the humanistic approach shows that basic needs are the needs owned by every human being that are urgent to be fulfilled. The basic needs appear in inner sense as a motivation of human activities to struggle.